2016
DOI: 10.1128/aem.04027-15
|View full text |Cite
|
Sign up to set email alerts
|

Silica-Induced Protein (Sip) in Thermophilic Bacterium Thermus thermophilus Responds to Low Iron Availability

Abstract: Thermus thermophilus HB8 expresses silica-induced protein (Sip) when cultured in medium containing supersaturated silicic acids. Using genomic information, Sip was identified as a Fe 3؉ -binding ABC transporter. Detection of a 1-kb hybridized band in Northern analysis revealed that sip transcription is monocistronic and that sip has its own terminator and promoter. The sequence of the sip promoter showed homology with that of the A -dependent promoter, which is known as a housekeeping promoter in HB8. Consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Although the maximum activity value achieved in a medium exchange culture was 3.6-fold higher than that observed before induction, this maximum activity was less than one-third of the value observed after an uninterrupted culture period in 10 mM silica. In a recent report, we similarly observed that medium exchange was ineffective in an E. coli-based protein expression system that utilizes silica as an inducer in advance [12]. As discussed in previous reports, this decrease in protein expression may be attributable to intracellular iron storage proteins.…”
Section: Effect Of Medium Exchange On Gene Expressionmentioning
confidence: 51%
See 4 more Smart Citations
“…Although the maximum activity value achieved in a medium exchange culture was 3.6-fold higher than that observed before induction, this maximum activity was less than one-third of the value observed after an uninterrupted culture period in 10 mM silica. In a recent report, we similarly observed that medium exchange was ineffective in an E. coli-based protein expression system that utilizes silica as an inducer in advance [12]. As discussed in previous reports, this decrease in protein expression may be attributable to intracellular iron storage proteins.…”
Section: Effect Of Medium Exchange On Gene Expressionmentioning
confidence: 51%
“…We previously reported that Thermus strains produced a specific Sip in the presence of supersaturated silica [12]. This Sip exhibited high homology with a Fe 3+ -binding ABC transporter that plays a role in Fe 3+ uptake.…”
Section: Construction Of a Silica-inducible Expression Vector And Repmentioning
confidence: 95%
See 3 more Smart Citations